Developing a preliminary ‘never event’ list for general practice using consensus-building methods - de Wet, Carl (Royal College of General Practitioners, 2014)
BACKGROUND: The ‘never event’ concept has been implemented in many acute hospital settings to help prevent serious patient safety incidents. Benefits include increasing awareness of highly important patient safety risks among the healthcare workforce, promoting proactive implementation of preventive measures, and facilitating incident reporting. AIM: To develop a preliminary list of never events for general practice. DESIGN AND SETTING: Application of a range of consensus-building methods in Scottish and UK general practices. METHOD: A total of 345 general practice team members suggested potential never events. Next, ‘informed’ staff (n =15) developed criteria for defining never events and applied the criteria to create a list of candidate never events. Finally, UK primary care patient safety ‘experts’ (n = 17) reviewed, refined, and validated a preliminary list via a modified Delphi group and by completing a content validity index exercise. RESULTS: There were 721 written suggestions received as potential never events. Thematic categorisation reduced this to 38. Five criteria specific to general practice were developed and applied to produce 11 candidate never events. The expert group endorsed a preliminary list of 10 items with a content validity index (CVI) score of >80%. CONCLUSION: A preliminary list of never events was developed for general practice through practitioner experience and consensus-building methods. This is an important first step to determine the potential value of the never event concept in this setting. It is now intended to undertake further testing of this preliminary list to assess its acceptability, feasibility, and potential usefulness as a safety improvement intervention.